Characteristics of medicinal plants traded in different popular markets of Lima Metropolitan Area and their effects on the environment and public health - Silva Alarcón, Jesús (2019)
Objective: To evaluate the characteristics of medicinal plants traded in different popular markets of Lima Metropolitan Area and their effects on the environment and public health. Materials and methods: A descriptive study was carried out in popular markets of Lima. Data was collected through semi-structured interviews and non-participant observation. The variables to be considered were common names, origin, retailing/wholesaling, part of the plant to be traded, reported use, seasonality and most demanded species. Specialized bibliography was reviewed to determine the origin of the species and their threat categorization for endangered wild flora species. Results: Two hundred ninteeen (219) species of medicinal plants were collected, out of which 183 were taxonomically identified and belonged to 65 botanical families, mostly Asteraceae (37) and Lamiaceae (17), some of them in danger of extinction. Conclusions: The plants mainly come from the Peruvian highlands and are marketed in "bundles". A same species whose demand is increased in winter (> 85 species) may be offered for the treatment of several health problems. The most frequently sold species are chamomile, oregano, cedron, melissa or lemon balm, lemon grass, fennel, muña (Minthostachys mollis), aloe, broadleaf plantain and coca. Out of the total number of species identified, 10 % is endangered.